If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6t + 8 = 8 + -1t Reorder the terms: 8 + 6t = 8 + -1t Add '-8' to each side of the equation. 8 + -8 + 6t = 8 + -8 + -1t Combine like terms: 8 + -8 = 0 0 + 6t = 8 + -8 + -1t 6t = 8 + -8 + -1t Combine like terms: 8 + -8 = 0 6t = 0 + -1t 6t = -1t Solving 6t = -1t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add 't' to each side of the equation. 6t + t = -1t + t Combine like terms: 6t + t = 7t 7t = -1t + t Combine like terms: -1t + t = 0 7t = 0 Divide each side by '7'. t = 0 Simplifying t = 0
| x-10Xx-10=102 | | -(5x-3)+3x-6=-3 | | 80x+60y=420 | | Y=3/4x=4 | | 3(7m-6)=15 | | 4x+3=15+7x | | 4x^2(256)=(1/16)^2x | | x+3=1-5x | | -6-10m=12n | | 6(x+3)+10=4(3x-4) | | 11p^2-3=5p | | 2x^2+25y^2=100 | | m=25+6 | | 512=2x | | 176-y=280 | | (3x-7)2= | | X^2+y^2-12x-4y+40=64 | | 22+2x=24 | | 0.7(2x+4)=1.1-(x+3) | | (4r+4)*5=8*(5r-10) | | y/5=7/11 | | 15(v+2)-3v=3(4v+2)-7 | | 3n-3+6=9 | | y/5=7/1 | | (4r+4)*5=8*(4r-10) | | 5+9=9+5 | | 5(f-8)=20 | | (4r+4)*5=8*(4r-8) | | 2(x+4)-3=-4(x-2)+8 | | [7*x]/2=28 | | (2r+4)*4=6*(4r-8) | | 4/8=n/4.6 |